2018
DOI: 10.1055/s-0038-1639370
|View full text |Cite
|
Sign up to set email alerts
|

Is the Oblique Branch a Preferable Vascular Pedicle for Anterolateral Thigh Free Flaps?

Abstract: The oblique branch is sufficiently large and can be reliably used as the flap pedicle. It may be the preferred vascular pedicle for ALT free flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(34 reference statements)
0
13
1
1
Order By: Relevance
“…23 While the oblique branch typically has a smaller vessel diameter and shorter pedicle length relative to the D-LCFA, its higher incidence of a septocutaneous course makes it preferable in certain situations due to an easier and quicker dissection. 24,25 Furthermore, it offers the additional advantage of being able to be raised as a single or multipaddle flap depending on recipient needs. 24,25 In a minority of cases, the oblique branch may be the only skin perforator, necessitating its preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 While the oblique branch typically has a smaller vessel diameter and shorter pedicle length relative to the D-LCFA, its higher incidence of a septocutaneous course makes it preferable in certain situations due to an easier and quicker dissection. 24,25 Furthermore, it offers the additional advantage of being able to be raised as a single or multipaddle flap depending on recipient needs. 24,25 In a minority of cases, the oblique branch may be the only skin perforator, necessitating its preservation.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Furthermore, it offers the additional advantage of being able to be raised as a single or multipaddle flap depending on recipient needs. 24,25 In a minority of cases, the oblique branch may be the only skin perforator, necessitating its preservation. In addition to different pedicles, varying pedicle branching patterns have been described.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of thighs (15) showed multiple perforators. An oblique branch 20,21 of the lateral circumflex femoral artery gave perforators in five thighs (25%). In one thigh, the oblique branch gave two perforators, for a total of six (11.8%) perforators arising from the oblique branch.…”
Section: Resultsmentioning
confidence: 99%
“…Such variation would be clinically relevant as recent work has recommended the oblique branch (if present) over the descending branch as a pedicle for the ALT flap. 20 Deng et al found that oblique branches were present in 34% of cases (echoing the 35% in Wong et al's initial description) and, when used as flap pedicles, yielded significantly more septocutaneous perforators, significantly shorter operating times and similar operative results when compared with the descending branch. As such, trainees may be encouraged to explore the oblique branch more readily and thus could be aided by a clearer description of any variations in BxJn anatomy specific to this branch.…”
Section: Furthermore Some Box Junctions May Require Sacrifice Of Thementioning
confidence: 90%
“…Wong et al confirmed that there are two variants of anatomical vascularisation of the ALT lobe in their study describing the exact anatomy of the vascular pedicle of ALT [ 12 ]. In most cases, the blood supply comes from the descending branch of the femoral artery; however, less commonly, the blood supply comes from the oblique branch of the circumflex artery [ 13 ]. In the present study, most of the flaps (> 97%) were vascularised through the descending branch.…”
Section: Discussionmentioning
confidence: 99%